Analisis penerapan metode storytelling sebagai upaya meningkatkan keterampilan berbicara siswa sekolah dasar pada p - Arida Kismatul Fatimah; Adinda Agustina Putri; Arini Mufi’ah; Della Ariska Dwi.P; Nadia Putri Indrianto; Vivi Rulviana (Universitas PGRI Madiun, 2026)
Conversational abilities are crucial for young learners in primary school, as they facilitate effective interaction and the sharing of thoughts. Nonetheless, numerous children continue to struggle with speaking confidently and articulating their ideas in a structured manner. This research focused on outlining how the storytelling technique can enhance speaking abilities in Indonesian language instruction. A descriptive qualitative method was utilized, involving a literature review that examined 16 pertinent national journal articles through content analysis. The results indicate that storytelling significantly boosts students' speaking abilities, which encompass fluency, vocabulary knowledge, pronunciation, intonation, self-assurance, and the capacity to convey thoughts logically. The effectiveness of this method is notably augmented when combined with appropriate teaching aids, such as storybooks, hand puppets, picture sequences, animated films, and audiovisual aids. Hence, storytelling is endorsed as a valuable educational approach to enhance the speaking skills of elementary school pupils.